1984
DOI: 10.1177/019262338401200308
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Regulation of Aryl Hydrocarbon Hydroxylase in Man: Studies with Liver, Lung, Placenta, and Lymphocytes

Abstract: Properties and response smoking of aryl hydrocarbon hydroxylase (AHH) activity in various human tissues are reviewed. In the placenta, induction of AHH by smoking can be demonstrated unequivocally. AHH activity in lung samples is variable, but the relation to current or past smoking i s unclear. The effect of cigarette smoking can be readily shown in the rate of antipyrine elimination, although there i s no change in AHH activity in liver biopsy samples. The reason for this discrepancy i s not known. In periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…However, animal experiments have demonstrated that the exposure to cigarette smoke does not induce hepatic xenobiotic metabolism, whereas the same treatment induces extrahepatic xenobiotic metabolism (for ref. see Pelkonen, 1976;Pelkonen et al, 1984;Vahakangas et al, 1983). The few available studies with human tissues have not yielded definitive results (Boobis et al, 1980;Pelkonen et al, 1975;Vahakangas et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, animal experiments have demonstrated that the exposure to cigarette smoke does not induce hepatic xenobiotic metabolism, whereas the same treatment induces extrahepatic xenobiotic metabolism (for ref. see Pelkonen, 1976;Pelkonen et al, 1984;Vahakangas et al, 1983). The few available studies with human tissues have not yielded definitive results (Boobis et al, 1980;Pelkonen et al, 1975;Vahakangas et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Pelkonen, 1976;Pelkonen et al, 1984). It is thought that the increase in the plasma elimination of a number of drugs is due to the induction of hepatic drug-metabolizing enzymes, but unequivocal proof in man has not been provided.…”
Section: Introductionmentioning
confidence: 99%
“…Once established, the AHH levels seem to persist for some weeks after removing the inducing stimulus [35]. In contrast to hepatic microsomes, placental microsomes with high AHH activity do not contain increased concentrations of the components for electron transport When compared to other human tissues, placenta responds sensitively to cigarette smoking [41,421. The dose-response curve between the number of cigarettes smoked daily and AHH activity is sigmoidal [43].…”
Section: B Aryl Hydrocarbon Hydroxylase Activity and The Metabolism mentioning
confidence: 99%
“…The elimination of several drugs is enhanced and the metabolism of polycyclic aromatic hydrocarbons (PAH) in certain human tissues is increased by cigarette smoking (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…The microsomal xenobiotic-metabolising system in the liver responds also to cigarette smoking, although to a lesser extent (1,3,4). However, estimation of the level of exposure to inducing agents, for instance cigarette smoke, is not an easy task.…”
Section: Introductionmentioning
confidence: 99%